Pengaruh Faktor Kepercayaan, Keamanan Transaksi dan Kualitas Pelayanan Terhadap Keputusan Pembelian Online pada Aplikasi Shopee Bagi Pengguna di Kota Depok - Novi Julianti; Helmy Ivan Taruna (Jurnal Manajemen Bisnis Digital Terkini, 2024)
. One of the most popular types of e-commerce today is the marketplace which is widely used by people to run businesses and helps them shop online to meet their needs. Shopee is one of them because it is often visited via the website. This research uses a quantitative approach method by utilizing primary data as a data source obtained from the results of a questionnaire in the form of a Google form. The analysis techniques used are data quality tests (validity and reliability tests), classical assumption tests (normality test, heteroscedasticity, multicollinearity and multiple linear regression), hypothesis testing (partial t test). ) and f test (simultaneous) and coefficient of determination test (R2). Data processing in this research uses SPSS version 25. Based on research, it shows that trust has a partial effect on purchasing decisions with a sig. 0.008. Transaction security does not partially influence purchasing decisions with a sig value. 0.296. Service quality partially influences purchasing decisions with a sig value. 0,000. So trust, transaction security and service quality influence decisions with a sig value of 0.015.